Relevance of Carrying Capacity and Eco-development Linkages for Sustainable Ecotourism - Bhattacharya, A. K.; Banerjee, Suchitra (Indian Forester, 2003)
The concept and significance of Carrying Capacity (CC) with respect to Sustainable EcoTourism (SET) has been explained and analysed in the paper. The emerging importance of CC and Eco-Development (ED) linkages in ecotourism and wildlife management has been addressed and critically examined. The scope of further research, methodology and bibliography for further readings in the field have been suggested.